2010
DOI: 10.1017/s1466252310000174
|View full text |Cite
|
Sign up to set email alerts
|

Toward a better understanding of pig behavior and pig welfare

Abstract: Pork production began to flourish in the USA after the practice of finishing pigs on corn was popularized in the late 1600s. By the 1840s, there were 35 million pigs and 20 million people in the USA and Cincinnati was the world's largest pork market. Between 1890 and the present, the total number of pigs in the USA has remained at 50-60 million, but dramatic changes in swine husbandry over the course of the 20th century have metamorphosed pig production from small, extensive (outdoor), labor-dependent enterpri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 72 publications
(88 reference statements)
0
52
0
3
Order By: Relevance
“…The most prominent species-specific behaviour of pigs is foraging-related rooting (Graves 1984). In natural environments pigs spend major parts of the day engaged in feeding and related behaviours (Kittawornrat & Zimmerman 2011). Although this is common knowledge, modern housing systems do almost entirely ignore this requirement on the pigs´ environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most prominent species-specific behaviour of pigs is foraging-related rooting (Graves 1984). In natural environments pigs spend major parts of the day engaged in feeding and related behaviours (Kittawornrat & Zimmerman 2011). Although this is common knowledge, modern housing systems do almost entirely ignore this requirement on the pigs´ environment.…”
Section: Introductionmentioning
confidence: 99%
“…The behavioural repertoire of the pig includes a large range of exploratory behaviours and a high motivation to forage and manipulate substrate (Day et al 1995, Kittawornrat & Zimmerman 2011. The feed is found and fed in small bouts, the feeding rate therefore low growing pigs a beneficial effect might be found.…”
Section: Introductionmentioning
confidence: 99%
“…Sense of smell The olfactory system, or sense of smell, of pigs is considered to be their most acute sense (Guntherschulze 1979;Graves 1984;Croney et al 2003;Kittawornrat and Zimmerman 2011). Olfaction plays a key role in navigation through their environment.…”
Section: Physiological Senses Driving Motivationmentioning
confidence: 99%
“…Despite high levels of curiosity in domestic pigs (Wood-Gush and Vestergaard 1991;Kittawornrat and Zimmerman 2011), wild pigs are highly sensitive to changes in their environment and often alter their behaviors in response to new objects (Muir and McEwen 2007;Campbell et al 2010). Additionally, commonly used attractants (e.g., corn) oftentimes appeal to non-target species resulting in increased costs and missed opportunity (e.g., tripped traps).…”
Section: Introductionmentioning
confidence: 99%
“…Physiological and behavioural studies have identified noise stress during housing (Schäffer et al, 2001;Kittawornrat and Zimmerman, 2011). Pigs exposed to 90 dB of prolonged or intermittent noise increased cortisol, ACTH and the noradrenaline-to-adrenaline ratios (Otten et al, 2004).…”
Section: Introductionmentioning
confidence: 99%